Taxonomic revision of the leafhopper tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) from China, with description of new taxa - Viraktamath, C. A.; Dai, Wu; Zhang, Yalin (Zootaxa, 2012)
The leafhopper tribe Agalliini from China is reviewed. The Chinese fauna includes 44 species of 15 genera including four new genera: Purvigallia gen. nov. (type species: Purvigallia maculata sp. nov., from Yunnan), Skandagallia gen. nov. (type species: Skandagallia dietrichi sp. nov., from Yunnan), Sinoagallia gen. nov. (type species: Sinoagallia serrata sp. nov., from Yunnan) and Sungallia gen. nov. (type species: Sungallia truncata sp. nov., from Yunnan). Japanagallia is the most species rich and includes 17 species from China, of which five are new: Japanagallia curvipenis sp. nov. (China: Xizang), Japanagallia decliva sp. nov. (China: Shaanxi), Japanagallia multispina sp. nov. (China: Guangxi, Guizhou, Shaanxi, Yunnan), Japanagallia palmata sp. nov. (China: Yunnan) and Japanagallia sclerotica sp. nov. (China: Shaanxi). The genus Igerna Kirkaldy (with Igerna channa sp. nov from Guangxi and Tibet) and the European species, Anaceratagallia ribauti (Ossianinilsson) have been recorded for the first time from China. All the new taxa are described and illustrated. A check-list with taxonomic notes as well as a generic key to Chinese Agalliini are also provided.